Saved by a giant gourd: Political reality and philosophical deactivation of the counsellor in the Zhuangzi - Galvany, Albert (Asian philosophy, 2025)
Placed in the first chapter of the Zhuangzi, the dialogue between Huizi and Zhuangzi about a giant gourd is a celebrated anecdote that, both for its structure and for the ideas it seems to mobilize, has aroused the interest of readers and, consequently, has also generated a wide variety of interpretations. While some scholars argue that the message is part of a framework of epistemological discussion, others point to perspectivism as the hermeneutical key to the passage, while others refer to the idea of anti-anthropocentrism. Based on an analysis of the biographical elements that can be extracted from the story, the way in which the metaphor of useless gourds is used in the philosophical literature of the time and the central role played in it by the figure of the thinker-counsellor, this article reconsiders the story from an alternative angle that privileges a political perspective.